PENGEMBANGAN FORMULA REMPEYEK KOIN TERIYUMMY BERDASARKAN ANALISIS SENSORI - Nur Faizah, Risma; Sholiha, Illiyatus (Jurnal Perikanan Pantura (JPP), 2025)
Rempeyek is a traditional snack made from rice flour that is fried thin and crispy, with added peanuts as a complement. Innovation in developing coin rempeyek made from anchovies Stolephorus sp. was carried out to increase nutritional value, attractiveness, and provide new variations to traditional foods. This study aims to develop a Teriyummy Coin Rempeyek formula made from anchovies, while determining the best formula based on organoleptic observations. Three formulas were tested (Formula I, II, and III) with variations in ingredient composition, molding methods, and oil draining techniques. Quality assessment was carried out through sensory tests on parameters of appearance, aroma, taste, and texture, which were then processed into sensory values ​​P. The results showed that the development of the Teriyummy coin rempeyek formula based on sensory analysis was carried out through three stages of formula development. The results of the sensory analysis of Formula I and II have not met the sensory quality criteria based on SNI, while Formula III provides sensory values ​​that have met the SNI quality criteria (min 7) namely appearance parameters: 8, Smell: 8, Taste: 8, Texture: 8, formula improvements through the use of special molding tools, not using red chilies and tapioca flour. Anchovies are replaced with anchovies, the addition of roasted candlenuts and the use of a spinner as a draining tool. The final formula of Teriyummy coin rempeyek based on sensory analysis is formula.